Knee osteotomies significantly influence coronal ankle alignment: A radiographic analysis - Alessio Maione; Carlo Minoli; Matteo Davide Parmigiani; Martino Travi; Filippo Calanna; Daniele Marcolli; Riccardo Compagnoni; Paolo Ferrua; Massimo Berruto; Pietro Simone Randelli (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose This study aimed to evaluate the effect of lateral closing‐wedge high tibial osteotomy (LCW‐HTO) and medial closing‐wedge distal femoral osteotomy (MCW‐DFO) on tibio‐talar inclination (TTI) and Mikulicz lateral distal tibial angle (M‐LDTA). We hypothesized that knee osteotomies significantly alter ankle coronal alignment by modifying TTI and distal tibial alignment in relation to the mechanical axis. Methods A retrospective radiographic analysis was conducted on 60 knees from 52 patients (37 LCW‐HTO and 23 MCW‐DFO) treated between 2006 and 2020. Inclusion criteria included full‐length weight‐bearing radiographs pre‐ and post‐operatively, no prior ipsilateral lower limb surgery, absence of shaft deformities or advanced ankle osteoarthritis (Takakura grade >1), and age ≥16 years with ≥2 years of follow‐up. Radiographic parameters measured included LDTA, hip‐knee‐ankle angle, M‐LDTA and TTI, with ankle realignment quantified through differences between LDTA and M‐LDTA and between pre‐ and post‐operative TTI. Results In the MCW‐DFO group, the difference between LDTA and M‐LDTA decreased from 3.5 ± 2.3° to 1.3 ± 1.1° (p < 0.0001), indicating improved alignment. The LCW‐HTO group showed a smaller but significant reduction from 4.5 ± 1.8° to 2.2 ± 1.7° (p < 0.0001). TTI improved significantly in both groups, with a greater adjustment in MCW‐DFO (ΔTTI = 7.0 ± 4.3°, p < 0.01) compared to LCW‐HTO (ΔTTI = 4.2 ± 2.7°, p < 0.01). The difference between LDTA and TTI decreased in both groups, reflecting post‐operative convergence of the mechanical and anatomical axes. Conclusion Knee osteotomies significantly influence ankle coronal alignment, particularly modifying TTI and M‐LDTA. Higher‐level osteotomies (MCW‐DFO) exert a greater effect on ankle alignment than LCW‐HTO. Preoperative valgus or varus knee deformities must be carefully evaluated to anticipate post‐operative ankle imbalance. Surgeons should assess full‐length radiographs to prevent unintended malalignment. Level of Evidence Level III.